Women’s participation in education and politics: evidence from the selected OIC countries - Haque, M. Faizul; Chowdhury, Mohammad Abdul Matin; Ahmad, Nadzrah; Rakibuddin, Mohammad (Asian Institute of Research, 2020)
In this twenty-first century, it is crystal clear that education is the most powerful instrument for a nation’s progress and prosperity. Islam has also emphasized on educating both men and women since the beginning. So, Muslim countries should take initiatives to enhance participation of women in education. In reality, it is seen that women’s positions in the field of education and politics are very nominal compared to their male counterparts within Muslim countries. Situation is even worse in under-developed and non-democratic countries where the position of women and their participation in both the education and political sectors alongside men are visibly low. In this context, the purpose of this study is to explore the level of Muslim women’s participation in education and politics in some selected Muslim countries. Two South-Asian countries, Bangladesh and Pakistan, two south-east Asian countries, Malaysia and Indonesia, and the Middle East and North Africa (MENA) countries have been considered for this study. Thus, empowered women can take part in politics to resolve social issues. One of the findings of this study is that in democratic countries such as; Malaysia, Indonesia, and Bangladesh, women’s participation in both the educational and political sectors have been significantly improving over the years. Though economic conditions and social stigma, directly and indirectly, are still the barriers to enhance women’s education level as well as their participation in politics. Finally, the study highlights the obstacles that hinder women’s participation in both sectors and discusses the remedies to overcome the situation from an Islamic point of view.